Suberin and hemicellulose in sugarcane cell wall architecture and crop digestibility: A biotechnological perspective - Raquel Figueiredo; Pedro Araújo; Juan Pablo P. Llerena; Paulo Mazzafera (Food and Energy Security, 2019)
Abstract Sugarcane is a highly efficient biomass producer used in the last decades for bioethanol and bioelectricity production, as well as for animal feeding. Together with lignin, suberin is a major factor for the low sugarcane biomass digestibility by ruminants. The lipid–phenolic biomolecular composition and the ultrastructure of suberin and associated waxes confer them extraordinary properties of hydrophobicity, flexibility, and anti‐microbial resistance, responsible for the low digestibility of suberized tissues. Additionally, hemicelluloses cross‐linked with suberin and lignin also contribute appreciably to cell wall recalcitrance. In this review, a main focus was given to suberin and secondly to hemicellulose and how they may interfere with ruminant digestibility. Suberin and hemicellulose deposition and biomolecular composition are genetically regulated, showing a close regulatory interplay with phenylpropanoid and fatty acid biosynthesis pathways, cutin disruption, and stress and defense responses. Understanding the bulk of transcription factors network and hormonal regulatory mechanisms will allow accurate biotechnological approaches to the production of more feasible forage sugarcane.